Advances and challenges in commercializing radiative cooling. (December 2019) - Liu, J.; Zhou, Z.; Zhang, J.; Feng, W.; Zuo, J.
Abstract: Radiative cooling (RC) dissipates terrestrial heat to outer space through the atmospheric window, without external energy input and production of environmental pollutants. More and more efforts have been devoted to this clean promising cooling technology; thus diverse radiative coolers have emerged. However, the performance, cost, and effectiveness of various radiative coolers are not exactly the same. In addition, the large-scale application of RC technology is impeded by the low energy density, uncontrollable cooling power, and limited sky-facing area. Here, we critically review the recent progress of RC technology, evaluate the cooling performance of various radiative coolers, and discuss the challenges and feasible solutions to commercialize RC technology. Furthermore, valuable insights are provided to make new breakthroughs in this field. Graphical abstract: Application and classification of radiative coolers. Main applications include building cooling (BC), photovoltaic cooling (PC), cryogenic cooling (CC) and energy harvesting (EH). We classify the recently proposed radiative coolers according to the thermal infrared emissivity inside and outside the atmospheric window. Image 1 Highlights: The recent progress in radiative cooling (RC) was critically reviewed and summarized. The performance of various radiative coolers was evaluated according to more explicit standard. The challenges and feasible solutions to commercialize RC technology were discussed. Valuable insights into the application of RC technology were provided.